Tubercular hemoptysis in a young liver transplanted patient: Case report. Issue 33 (August 2019) - Di Dato, Fabiola; Nunziata, Francesco; Rosa, Margherita; Iorio, Raffaele; Spagnuolo, Maria Immacolata
Abstract: Rationale: Liver transplanted patients have excellent survival rates, but infectious complications are a major cause of morbidity and mortality. Diagnosis and treatment of tuberculosis (TB) in liver recipients are very challenging. Specific recommendations for anti-TB treatment in liver transplanted patients are lacking. Patient concerns and diagnosis: A 22-year-old male liver transplanted patient because of biliary atresia showed unexpected acute hemoptysis while he was on immunosuppressive therapy with tacrolimus and mycophenolate mofetil. Computed tomography (CT) identified a pulmonary arteriovenous malformation (PAVM) successfully treated with endovascular embolization. A post-embolization thoracic CT revealed pulmonary cavitation and miliary pattern suggesting pulmonary TB causing PAVM. TB diagnosis was confirmed by microbiological assays and genetic amplification techniques. Intervention: Anti-TB 4-drug regimen was started. Following the beginning of treatment, liver enzymes increased. In order to clarify if liver cytolysis was due to hepatotoxicity or hepatic rejection linked to the reduction of immunosuppression or a worsening of pre-existing graft hepatitis, a liver biopsy was performed. A mild graft rejection was found so that tacrolimus doses were increased despite the risk of tubercular dissemination. Outcome: The patient completed anti-TB therapy in 8 months with resolution of TB disease and stable liver disease. Lessons: TB management in liver transplanted patients is challenging and needs to be individualized especially if chronic graft hepatitis is present.